P135 Atopic dermatitis is associated with the clinical course of inflammatory bowel disease. (30th January 2023) - Kim, K W; Koh, S J; Kang, H W; Park, H; Ha, H; Park, J; Kim, K; Jun, Y; Lee, H J; Yoon, H; Im, J P; Park, Y S; et al.
Abstract: Background: There are a few studies about the relationship between inflammatory bowel disease (IBD) and atopic dermatitis (AD). It implies that both diseases have common pathophysiologic mechanisms and can affect each other. However, little information is available on the effect of AD on the clinical course of patients with IBD. Methods: This is a multicenter, retrospective, observational study. Patients with concurrent IBD and AD were defined as case group. AD was defined as chronic eczematoid dermatosis diagnosed by dermatologists. Age-, gender-, and IBD subtype-matched patients without AD were included as reference group. The ratio of the case and reference group is 1:2. Results: The numbers of patients in the case and reference group were 61 and 122, respectively. There was a significantly shorter biologics-free survival in the case group than that in the reference one after the multivariable adjusted Cox regression analysis with the onset age, disease duration, smoking status, use of steroid, use of immunomodulator, presence of other allergic diseases and initial disease severity [hazard ratio (HR) 1.743, 95% confidence interval (CI) 1.048-2.901, p = 0.032]. The trend was shown consistently in the subgroup analysis with ulcerative colitis (HR 4.769, 95% CI 1.625-13.995, p = 0.004), but not with Crohn's disease (HR 1.393, 95% CI 0.736-2.636, p = 0.308). Conclusion: AD showed a significant effect on the biologics-free survival of patients with IBD, especially UC. Further mechanistic research is required to elucidate the pathogenesis of AD on the clinical course of IBD.